The changing face of religion and human rights : a personal reflection - Nathan, Clemens N. (Clemens Neumann), 1933-2015 (M. Nijhoff Publishers, 2009)
Clemens N. Nathan has devoted a lifetime to the pursuit of Human Rights to understanding.